Medidas de política monetária e estabilidade de inflação em países emergentes - Zaidan, Marta Penteado (2007)
The goal of this paper is to evaluate the validity of Taylor principle when it comes to controlling inflation in seven developing countries that use inflation targeting regimes: Brazil, Colombia, Mexico, Philippines, Poland, South Africa and Turkey. The test is based on a state-space model to determine when each country have followed the principle, then, a threshold unit root test is used to verify if the stationarity of the deviation of the expected inflation in relation to the target depends on the compliance with Taylor principle. The results show that the compliance with Taylor principle leads to the stationarity of the deviation of the expected inflation in relation to the target in all cases. Furthermore, in most of the cases the non-compliance with Taylor principle leads to a non-stationary deviation of the expected inflation.